Do pictures really say more than a thousand words? A network approach to early traumatic experience and empathic responding. Issue 1 (31st December 2020) - Mueller, Sven C.; Hudson, Anna R.; Meeus, Carmen
ABSTRACT: Background: Empathy is essential for interpersonal relationships, yet remains difficult to measure. Some evidence suggests that early traumatic experiences leads to alterations in empathic responding. Objective: This study sought to differentiate connections between subtypes of childhood maltreatment, a pictorial test of affective empathy (PET), and self-reported empathy (Interpersonal Reactivity Index; IRI) by using network analysis approach to investigate the structure of relationships between childhood maltreatment and later empathic responding. Method: 301 participants completed the PET, the Early Trauma Inventory Self Report-Short Form (ETISR-SF), the IRI, and questionnaires assessing current mood and perceived stress levels. Results: The PET showed a strong positive association with the IRI subscale empathic concern (EC), after conditioning on all other nodes in the network. EC proved to be a highly central node and was positively related to severity of childhood sexual abuse (CSA), yet not to childhood physical abuse or emotional maltreatment. Pathways between emotional maltreatment and physical abuse and the PET were indirect, passing through self-reported EC and CSA. Conclusions: Our study suggests that CSA more so than other childhood maltreatment experiences is associated with increased self-reported affective empathy, but is not captured directly through a pictorial test of affective empathy.